Penegakan hukum Terhadap Pelanggaran Hak Cipta VCD di Yogyakarta: Studi Kasus di POLDA DIY - Arif Budi Utomo (UIN Sunan Kalijaga Yogyakarta, 2014)
At this time, Copyright protection in Indonesia has undergone many changesand improvements. the protection egulated in Law Number 19 of 2002 on Copyright.But the reality is just the opposite occurs, more people who violate copyright. Widespreadcirculation of VCD, CD / MP3 and DVD piracy in the region that includes the cityof Yogyakarta Kota Gede Market and along the way Mataram is one indication of therising Copyright infringement. The data obtained from the Yogyakarta police during2005 through 2013, only one case has been handled. From the background of theproblem it may be withdrawn at issue as follows: 1. How does law enforcement againstviolators Copyright in Yogyakarta, 2. What are the constraints faced by theYogyakarta police in handling cases of rights violations in the region of Yogyakarta.The results of these studies are Yogyakarta police use two ways to deal with cases ofCopyright infringement in Yogyakarta. These efforts include enforcement (repressive)consisting of inquiry, investigation, arrest, searching and foreclosure and prevention(preventive) consisting of dissemination to the public on Copyright and meetingcoordination with the Province Government of Yogyakarta. Barriers experienced byYogyakarta police on law enforcement efforts include: economic background of the peopleof Yogyakarta, counterfeit of goods coming from outside Yogyakarta, lack of publicawareness regarding the protection of the Copyright, the lack of cooperation on the partof traders to prevent violations of rights in Yogyakarta.